Osteomyelitis of the Mandible after Dental Implants in an Immunocompetent Patient - Matthieu Balanger; Margaux Hinet; Christian Vacher; Norbert Bellaiche; Jean-Luc Charrier; Sarah Millot (Case Reports in Dentistry)
Dental implants are now broadly used to replace missing teeth, and the presence of infectious complications is rising. Dental implant therapy as a local risk factor for the onset of osteomyelitis and its management have not been widely explored. Here, we report an unusual case of mandibular suppurative osteomyelitis caused by Streptococcus intermedius in a healthy and immunocompetent patient secondary to mandibular implants. We describe how surgery combined with systemic application of antibiotics allowed conservation of the dental implants in the mandibular bone, discuss the probable source of contamination, and present the follow-up of the osteomyelitis.